Multimedia-Based Learning Media for I'tikad 50 at Dayah Darusysyari'ah - sriwinar sriwinar; Qamar Syafawi; Cut Rahmawati; Fitri Rizani (Universitas Malikussaleh, 2026)
This study aims to develop and test the effectiveness of interactive multimedia-based learning media on the I'tikad 50 material in Islamic boarding schools. The background of this study is the dominance of conventional learning methods in delivering aqidah material, making it less interesting and making it difficult for students to understand abstract concepts. The learning media developed is interactive multimedia based on Adobe Flash that combines various elements such as material text, audio narration, interactive animation, and evaluation quizzes with direct feedback. This media is designed with an attractive and interactive display to increase student involvement in the learning process. The results of validation by material experts and media experts indicate that the developed learning media is in the very feasible category. The results of trials with students show an increase in understanding of the I'tikad 50 material, which is seen from the increase in learning outcomes. In addition, this media is also able to increase students' interest and motivation to learn. The solution offered in this study is the use of Adobe Flash-based media is effective in increasing students' understanding and motivation to learn, and can be used as an innovative alternative to overcome the limitations of conventional learning methods in Islamic boarding schools. Thus, the use of interactive multimedia based on Adobe Flash has proven effective as an innovative learning media in Islamic boarding schools.